Implementation of the fiscal compact in the Euro area member states: Expertise on the behalf of the German Council of Economic Experts - Heiko T. Burret; Jan Schnellenbach (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2014)
[Conclusion] The overall picture of the current status of implementation of the Fiscal Compact into national law is rather ambiguous. On the one side, there are countries like Spain and Portugal, which have been severely affected by the Euro crisis, and appeared to have learned a lesson and implemented promising and strong fiscal rules. On the other side, it is worrisome that Greece, of all countries, has not put forward any draft bill so far and failed to meet the deadlines set by the MoU. The overall picture is also somewhat ambiguous because many countries have not anchored their budget rules into their constitution, but rely on simple laws instead. While the vast majority of countries have created the legal basis for the creation of an independent fiscal council, only some have already appointed the members. There seems to be a general tendency towards staffing the councils with members who are rather not involved in politics but are academic economists, and in some cases even are recruited from other countries. This finding fuels the expectation that the fiscal councils are not only de jure but also de facto independent in their work. However, one also has to note that the appointing process for fiscal councils is still a much politicized procedure, with the parliament and the government being the key players. Thus, the question to what extent the independence of the fiscal councils will also be ensured in the long run, remains unanswered for the moment. In some countries the independence is not institutionally secured, for instance, by explicitly prohibiting the appointment of active (or recently active) politicians for the fiscal council.
Keywords: 330